Expectativas e jurisdição : a cultura autoritária como condicionante da atuação do julgador no processo penal - Oliveira, Daniel Kessler de (2021)
In the brazilian law enviroment, betting in the imparciality of the judge is a commom sense. In history, we could point several examples that could demonstrate how much this stablishment embraces the brazilian law culture. This tradition presents itself fueled by an structural autoritarism, a hughe tolerancy for the etical issues of a few ones and a ‘zero tolerance’ speetch to other specific cases. A polarization status that reduces the complexity of the subjetcts in the criminal law procedures and encourages an iron fist atuation of the law, pervaded with several basic rights beeing violated in order to preserve the autority of the State, in this cenary, presented by the judge figure. Characterized by the culture sense, the judge goes thru the process totaly influenced by many public expectations, from all sorts and this expectations projects a script of actuation. It is wanted from the judge that he acts in a certain order and this is the main issue of the question in a matter of criminal law application. From all possible awnsers we get more doubdt that certains, and this demands a reflection in order to work seeking a damage reduce politic under the penalty of getting into the so criticated ‘reducionism’. Nonetheless, this expectations created could be a matter of social issues, political issues, lawfare and so many others issues and also conduce to a fullfilment ideia that coud be used by the judge to awnser the expectations in order to avoid the missconducts of the state judges. So, the judge distorces the law interpretation in order to attend the expectation when he should be encouraged to apply the law, despite the public opinion on that matter.The effects of this method on the brazilian criminal law procedure are overwhelming, going thru law makeovers and brand new jurisprudential interpretations, putting into the light all the sintoms due this autorithy infrastructure in criminal law procedure. This effects goes beyond the limits of a concrete case, in a determinated trial, mixing itself with political issuals and, thru this, in the very life standards of a nation citizens. This is extremely noticeable in many famous trials in Brazil such as the ‘mensalão trial’ or even the former president, Mr. Lula da Silva, trial, the so called ‘Lava-Jato’ trial (carwash-trial). The legacy of such developments to the brazilian law procedure study stills uncertain. Only time will assure what will happen in matter of criminal law security, but the reflection that is demanded is to assure if its possible to rescue the democratic brazilian law procedure or if we are in a hole diferent way of dealing with this matter, witch will end in his burial when it should be the most fundamental garanty against the autoritarism of the State